Study, Optimisation and Numerical Simulation of Natural Convection around the Radial Heat Sink: Optimization of Radial Heat Sink for Enhanced Natural Convection (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This work is on numerical study of natural convection around a radial heat sink having circular base and rectangular fins of various configurations using ANSYS WORKBENCH version 15.0. The material under consideration is aluminium and the free stream fluid is air. The heat transfer rate from the fins, outer wall and the overall heat transfer rate has been evaluated and compared for variety of fin configurations. Surface Nusselt number and surface overall heat transfer co-efficient has been found out. Temperature contours for different fin configuration has been plotted showing the convection currents formed around the heated fin. Velocity contours for various fin configurations also plotted and the motion of heated fluid is shown. Plots for Nusselt number and heat transfer co-efficient are also shown.The aim of the work is to optimize the existing radial fin. The objective is to increase the heat transfer from the source to the ambient air. This can be achieved by reducing the thermal resistance or by increasing the surface area for the natural convection. In this study the effect on natural convection by different geometrical modification is studied. In this study, natural convection from a heat sink with a circular base and rectangular fins is numerically analyzed, and the thermo-flow pattern is observed. The effects of the holes, slots number of holes and slots, slot length, slot height, hole diameter and heat flux on the thermal resistance and the average heat transfer coefficient are investigated. Study is also carried out on optimizing the existing radial heat sink by changing the mass distribution configuration.